Study on the adsorption of phosphorus from phosphorus-containing wastewater using composite mineral-based adsorbent materials derived from phosphate tailing - Yihuai Su; Hongwei Wei; Ting Xu; Zeming Shi; Chengwen Wang (Minerals Engineering, 2026)

Enhancing source-level DC component of AC triboelectric nanogenerator via mirror asymmetry mechanism - Zhaojuan Shi; Sheng Zhang; Menghe Gao; Wenxuan Li; Yinxi Da; Zeming Guo; Jianjun Li; Qiang Tang; Cheng Xu (Chemical Engineering Journal, 2026)

Non-additive effects of microplastics, atrazine, and sulfamethoxazole co-exposure on Penaeus vannamei health and environmental risks - Yinan Wang; Qiangqiang Shi; Weijia Gan; Feng Xu; Hao Liu; Liuquan Zhang; Rongrong Zhang; Jiong Chen; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2026)

Endoplasmic reticulum stress mediates oxidative stress-driven endothelial impairment and atherogenesis induced by sodium perfluorononenoxybenzene sulfonate exposure - Boxiang Zhang; Zeming Liu; Qing Li; Mingming Tian; Yue Gao; Hiroko Kishi; Dan Xu (Environmental Research, 2026)

Causal Transformer for Learning Embeddings from Structured Medical History Records and Multi-Source Data Integration for Complex Disease Risk Prediction - Zeming Li; Yu Xu; Debajyoti Chowdhury; Hip Fung Yip; Chonghao Wang; Lu Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)
Traditional disease risk prediction models predominantly rely on statistical algorithms and often focus on genetic factors or a limited set of lifestyle factors to estimate the risk of disease onset. Recently, more comprehensive approaches have emerged that integrate genetic factors with additional lifestyle factors (e.g., alcohol intake) and physical features (e.g., body mass index, age) to increase predictive accuracy. Since the onset of complex diseases is often accompanied by the occurrence of comorbidities, incorporating medical history records is a critical yet underexplored avenue for improving risk prediction. In this study, we propose a novel framework, MIDRP (Multi-source Integration for Disease Risk Prediction), which incorporates genetic variants, lifestyle factors, physical attributes, and medical history records to achieve more robust and accurate predictions. At the heart of our approach lies a causal Transformer architecture, specifically designed to extract and interpret nuanced patterns from medical history records. In the experiments, we compared MIDRP with several baselines, including LDPred2, random forest, multilayer perception, logistic regression, AdaBoost, DiseaseCapsule, EIR, and Med-Bert, on three complex diseases Coronary Artery Disease, Type 2 Diabetes, and Breast Cancer using data from the UK Biobank. Our method achieved state-of-the-art performance, AUROC scores of 0.783, 0.841, and 0.784, respectively, demonstrating its potential in the field of complex disease risk prediction.

Performance study on a cryogenic bubble pump for low-flow-rate liquid nitrogen transfer - Yuhui Chen; Ya Xu; Daming Sun; Zeming Wang; Qie Shen (International Journal of Refrigeration, 2026)

Spatio-temporal variations of heavy metal(loid)s and their influencing factors in surface sediments of Daya Bay, South China Sea - Zeming Wang; Nan Zheng; Man Hao; Yahui Xu; Jinmei Li (Frontiers in Marine Science, 2026)
To elucidate the spatiotemporal dynamics and driving mechanisms of heavy metal (loid)s (HMs) in coastal systems, this study investigated the surface sediments from Daya Bay across four seasons. Results indicated that the average HM concentrations (mg/kg) decreased in the order of Zn (65.35) > Pb (28.66) > Cu (13.19) > As (7.06) > Hg (0.073) > Cd (0.058), with Pb, As and Hg exhibiting significant seasonal heterogeneity ( p < 0.05). The Geo-accumulation Index ( I geo ) and Contamination Factor identified Hg as the dominant contaminant, registering the highest average I geo value of 2.039. Overall, the surface sediments in the study area exhibited a moderate level of cumulative pollution with an average Pollution Load Index (PLI) of 2.48, following a seasonal decline of winter (2.76) > spring (2.49) > autumn (2.39) > summer (2.27). Crucially, Redundancy Analysis revealed that the distribution of Cu, Zn, Cd, and Pb was primarily governed by natural physicochemical binding to fine-grained, organic-rich matrices. In contrast, the accumulation of Hg and As exhibited a stronger dependency on dynamic biogeochemical factors, notably dissolved oxygen and anthropogenic nutrient inputs. These findings highlight the necessity of distinct management strategies that account for the coupling between sediment matrices and water column biogeochemistry.

Customizable sub-nanometer vertical-step grayscale lithography - Haonan Ma; Shijie Zhao; Xia Liu; Ziying Hu; Xu Han; Hongtao Li; Zeming Jin; Mingdi Zhang; Jixiang Li; Wenke Fu; Yunyun Dai; Yuan Huang; et al. (Science Bulletin, 2026)

A durable immuno-protective core-shell microgel for the enhanced pancreatic islet transplantation in diabetes therapy - Zeming Hu; Yang Luo; Muhammad Junaid; Rong Xu; Yaoqi Chen; Jie Yao; Renhao Ni; Tong Zhu; Hua Zhang; Huiqing Ding; Yabin Zhu (Chemical Engineering Journal, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

Critical control points in Penaeus vannamei aquaculture: Dynamic tracking and comprehensive risk assessment of antibiotics - Feng Xu; Chenxue Yang; Hua Liu; Hao Liu; Mingze Chen; Yinliang Wu; Xizhi Shi; Zeming Zhang; Rongrong Zhang (Journal of Hazardous Materials, 2025)

Development and swallowability evaluation of easy-to-swallow anthocyanin-loaded ROS-responsive hydrogels - Yumeng Wang; Siyi Tang; Meili Xin; Zhiying Li; Guoli Ao; Xu Xie; Yihan Li; Zijing Li; Zeming Wang; Xilin Wu; Jinlong Tian; Bin Li (Innovative Food Science & Emerging Technologies, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Unraveling the pharmaceutical footprint and risks of combining different aquaculture modes and tailwater treatment systems - Feng Xu; Yangcai Wang; Qiangqiang Shi; Yinliang Wu; Zeming Zhang; Xizhi Shi (Aquaculture, 2025)

Combined ecotoxicity of polystyrene microplastics and Di-(2-ethylhexyl) phthalate increase exposure risks to Mytilus coruscus based on the bioaccumulation, oxidative stress, metabolic profiles, and nutritional interferences - Yinan Wang; Qiangqiang Shi; Menglan Zhang; Lingyan Xu; Qiang Wei; Rongrong Zhang; Aili Sun; Yin Lu; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2024)

Insights into oral lentinan immunomodulation: Dectin-1-mediated lymphatic transport from Peyer's patch M cells to mononuclear phagocytes - Kaiping Wang; Yuxuan Liu; Zeming Zhang; Ziming Zheng; Wenqi Tang; Wangtianzi Teng; Xu Mu; Jinglin Wang; Yu Zhang (Carbohydrate Polymers, 2024)

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

Ions release stages of Cu-Pb-Zn mine tailings waste: A column leaching simulation - Lei Xu; Liang Tang; Zeming Shi; Jingsong Yang; Kunhao Shi; Haili Zhang; Yuting Yuan (Ore and Energy Resource Geology, 2024)

The crustal structure of southeast Tibet from joint inversion of surface wave dispersion and gravity anomaly data - Haopeng Chen; Ruirui Fan; Nanqiao Du; Feng Bao; Zeming Zhang; Xuelei Li; Fang Zou; Chuang Xu (Journal of Asian Earth Sciences, 2024)

Revisiting Neoproterozoic tectono-magmatic evolution of the northern margin of the Yangtze Block, South China - Peng Wu; Yuan-Bao Wu; Shao-Bing Zhang; Yong-Fei Zheng; Long Li; Ying Gao; Hao Song; Zhengqi Xu; Zeming Shi (Earth-Science Reviews, 2024)

Improvement of rat hepatocellular carcinoma model induced by diethylnitrosamine - Runzhui Lin; Sitian Xie; Fengjie Xu; Zeming Chen; Jianrui Liu; Xingmu Liu (Tissue and Cell, 2024)

Identification of groundwater hydrogeochemistry and the hydraulic connections of aquifers in a complex coal mine - Zeming Hou; Lei Huang; Shengwei Zhang; Xuan Han; Jiang Xu; Yanna Li (Journal of Hydrology, 2024)

Flexural behavior of wet panel-to-panel groove-and-tongue joints provided with lapped U-bars - Ao Dong; Zhenyu Li; Bin Rong; Changxiang Wang; Zeming Wang; Hui Xu (Engineering Structures, 2024)

Quantitative evaluation on phosphate adsorption by modified biochar: A meta-analysis - Zeming Xu; Changhui Zhang; Chunhong Zhang; Zhe Chen (Process Safety and Environmental Protection, 2023)

Geothermal springs with high δ13CCO2-DIC along the Xianshuihe fault, Western Sichuan, China: A geochemical signature of enhanced deep tectonic activity - Jinlong Liang; Yi Yu; Zeming Shi; Zhipeng Li; Yi Huang; Hao Song; Jinyong Xu; Xinyu Wang; Xiaocheng Zhou; Luyu Huang; Zebin Luo; Jue Tong; et al. (Journal of Hydrology, 2023)

Illumination Adaptive Multi-Scale Water Surface Object Detection with Intrinsic Decomposition Augmentation - Zhiguo Zhou; Zeming Li; Jiaen Sun; Limei Xu; Xuehua Zhou (Journal of Marine Science and Engineering, 2023)
Visual object detection is an essential task for the intelligent navigation of an Unmanned Surface Vehicle (USV), which can sense the obstacles while navigating. However, the harsh illumination conditions and large scale variation of the objects significantly harm the performance of object detection methods. To address the above problems, we propose a robust water surface object detection method named multi-scale feature fusion network with intrinsic decomposition generative adversarial network data augmentation (MFFDet-IDGAN). We introduce intrinsic decomposition as data augmentation for the object detection to achieve illumination adapting. And an intrinsic decomposition generative adversarial network (IDGAN) is proposed to achieve unsupervised intrinsic decomposition. Moreover, the multi-scale feature fusion network (MFFDet) adopts an improved bidirectional feature pyramid network (BiFPN) and spatial pyramid pooling (SPP) blocks to fuse features of different resolution for better multi-scale detection. And an improved weighted stochastic weight averaging (SWA) is proposed and applied in the training process to improve the generalization performance. We conduct extensive experiments on the Water Surface Object Detection Dataset (WSODD), and the results show that the proposed method can achieve 44% improvement over the baseline. And we further test our method on a real USV in the sailing process, the results show that our method can exceeding the baseline by 4.5%.

Simultaneous determination and dietary intake risk assessment of 60 herbicide residues in aquatic products - Xinru Yu; Feng Xu; Rongrong Zhang; Hua Liu; Aili Sun; Liuquan Zhang; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2023)

Implanting nitrogen-doped graphene quantum dots on porous ultrathin carbon nitride for efficient metal-free photocatalytic hydrogen evolution - Hanxiang Chen; Zhao Mo; Zeming Wang; Pengcheng Yan; Peipei Sun; Guanyu Wu; Jinyuan Zhang; Xianglin Zhu; Liang Wang; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

Relative reinforcing effects of dibutylone, ethylone, and N-ethylpentylone: self-administration and behavioral economics analysis in rats - Miaojun Lai; Dan Fu; Zeming Xu; Han Du; Huifen Liu; Youmei Wang; Peng Xu; Wenhua Zhou (Psychopharmacology, 2022)

Genome‐wide identification of the traf gene family in yellow catfish ( Pelteobagrus fulvidraco ) and analysis of their expression in response to bacterial challenge - Zhiwei Nie; Bo Wang; Zhixuan Zhang; Zeming Jia; Runjie Xu; Heyu Wang; Wei Zhou; Yifu Gong (Journal of Fish Biology, 2022)
Tumour necrosis factor (TNF) receptor‐associated factor (TRAF) is a receptor protein that has important functions in the immune system. Nonetheless, there have been few reports of traf genes in teleost fishes. The present study aimed to identify the traf genes from the genomic information of yellow catfish ( Pelteobagrus fulvidraco ). Eight traf genes were identified and named, which are distributed on different chromosomes but have similar conserved protein domains. Phylogenetic and syntenic analyses demonstrated conservation of traf genes during evolution. In addition, yellow catfish has the relatively rare traf1 and traf5 genes. Gene structure and motif analysis revealed the homology and distribution diversity of the traf genes. Quantitative real‐time reverse transcription PCR was used to study the expression patterns of traf genes in healthy fish tissues and after infection by Aeromonas hydrophila . The results demonstrated significant changes in traf gene expression, indicating a potential role in innate immunity.

Intravenous immunoglobulin is effective in alleviating hepatic ischemia–reperfusion injury: a rat model study - Zeming Chen; Runzhui Lin; Hua Zhuo; Fengjie Xu; Xingmu Liu (Molecular Biology Reports, 2022)

Space target detection in optical image sequences for wide-field surveillance - Dan Liu; Xiaodong Wang; Yunhui Li; Zeming Xu; Jianing Wang; Zhonghui Mao (International Journal of Remote Sensing, 2020)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

Mechanism of post-seismic floods after the Wenchuan earthquake in the upper Minjiang River, China - Ding Hairong; Li Yong; Shao Chongjian; Lauvence Svirchev; Xu Qiang; Yan Zhaokun; Yan Liang; Ni Shijun; Shi Zeming (Journal of Earth System Science, 2017)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

UHP metamorphic rocks from the Chinese continental scientific drilling project: I. Petrology and geochemistry of the main hole (0–2,050 m) - Zeming Zhang; Yilin Xiao; Zhiqin Xu; Jochen Hoefs; Jinsui Yang; Fulai Liu; J. G. Liou; Klaus Simon (Contributions to Mineralogy and Petrology, 2013)

Metabolic profiling based on LC/MS to evaluate unintended effects of transgenic rice with cry1Ac and sck genes - Yuwei Chang; Chunxia Zhao; Zhen Zhu; Zeming Wu; Jia Zhou; Yanni Zhao; Xin Lu; Guowang Xu (Plant Molecular Biology, 2012)

Channelized fluids in subducted continental crust: constraints from δD–δ 18 O of quartz and fluid inclusions in quartz veins from the Chinese Continental Scientific Drilling Project - Xiaoming Sun; Li Xu; Weidong Sun; Wei Zhai; Yeheng Liang; Qian Tang; Jinlong Liang; Zeming Zhang; Kun Shen; Fangyue Wang; Mingxing Ling; Robert E. Zartman (International Geology Review, 2011)

Ultrahigh‐pressure metamorphic records hidden in zircons from amphibolites in Sulu Terrane, eastern China - Fulai Liu; Zeming Zhang; Ikuo Katayama; Zhiqin Xu; Shigenori Maruyama (Island Arc, 2003)
The amphibolites occur sporadically as thin layers and blocks throughout the Sulu Terrane, eastern China. All analyzed amphibolite from outcrop and drill cores from prepilot drill hole CCSD‐PP1 and CCSD‐PP2, Chinese Continental Scientific Drilling Project in the Sulu Terrane, are retrograded eclogites overprinted by amphibolite‐facies retrograde metamorphism, with characteristic mineral assemblages of amphibole + plagioclase + epidote ± quartz ± biotite ± ilmenite ± titanite. However, coesite and coesite‐bearing ultrahigh‐pressure (UHP) mineral assemblages are identified by Raman spectroscopy and electron microprobe analysis as inclusions in zircons separated from these amphibolites. In general, coesite and other UHP mineral inclusions are preserved in the cores and mantles of zircons, whereas quartz inclusions occur in the rims of the same zircons. The UHP mineral assemblages consist mainly of coesite + garnet + omphacite + rutile, coesite + garnet + omphacite, coesite + garnet + omphacite + phengite + rutile + apatite, coesite + omphacite + rutile and coesite + magnesite. Compositions of analyzed mineral inclusions are very similar to those of matrix minerals from Sulu eclogites. These UHP mineral inclusion assemblages yield temperatures of 631–780°C and pressures of ≥2.8 × 10 3 MPa, representing the P–T conditions of peak metamorphism of these rocks, which are consistent with those (T = 642–726°C; P ≥ 2.8 × 10 3 MPa) deduced from adjacent eclogites. These data indicate that the amphibolites are the retrogressive products of UHP eclogites.